Winning fair labour standards for domestic workers: lessons learned from the campaign for a domestic worker bill of rights in New York state - Hobden, Claire (Geneva, 2010)
"This paper attempts to identify the core reasons for the success of the Domestic Workers United (DWU) Domestic Worker Bill of Rights Campaign while explaining how the strategies adopted overcame particular challenges."